Born to win? Investigating the relative age effects in the big five European women's football leagues - Pérez-González, Benito; Iván-Baragaño, Iyán; Bonal, José; León-Quismondo, Jairo; Fernández-Luna, Álvaro; Burillo, Pablo (Frontiers in Sports and Active Living, 2025)
IntroductionThis study examines the presence of the Relative Age Effects (RAEs) among players in the top five European women's football leagues during the 2023/24 season.MethodsA total of 1,634 professional players from the Women's Super League (England), Liga F (Spain), Frauen-Bundesliga (Germany), Serie A Femminile (Italy), and Division 1 Féminine (France) were analyzed. Birth date distributions were assessed to determine the prevalence of RAEs both collectively and within each league.ResultsPoisson regression analyses revealed significant overall RAEs, with a higher proportion of players born in the first semester of the year. Individually, significant RAEs were found in England, Spain, Italy, and France, while Germany did not exhibit statistically significant effects. When analyzed by playing position, significant RAEs were observed among goalkeepers and midfielders, but not among defenders and forwards.DiscussionThese findings highlight the ongoing influence of RAEs in elite women's football and underscore the need for strategies to mitigate its impact on talent identification and player development.